Barminomycin forms GC-specific adducts and virtual interstrand crosslinks with DNA. - Perrin, L C (1999)
The sequence specificity of the binding of barminomycin (SN-07 chromophore) to DNA was investigated using an in vitro transcription assay. It was found that this compound formed blockages to transcription, and these blocks were highly selective for 5'-GC sequences. The half-lives of the first seven transcriptional blockages at 37 degrees C were 14-130 min, plus one site >>200 min, with widely varying levels of essentially permanent blockages at each site (0-100%; average of 40%), indicative of considerable dependence on flanking sequences of adducts stability at individual GC sites. Barminomycin was also shown to form DNA virtual (i.e. functional) interstrand crosslinks. Such crosslinks were also relatively heat stable, with 40% of the DNA remaining crosslinked after heating at 90 degrees C for 5 min. The barminomycin-DNA adducts and crosslinks appear to be essentially identical to those formed between adriamycin and DNA. Whereas adriamycin requires prior activation with formaldehyde in order to form adducts and crosslinks, barminomycin behaves in all respects as if it is a pre-activated form of adriamycin.